Geografía del transporte vial en Lima Metropolitana y su impacto ambiental territorial - Quispe Cornejo, Silvia (2007)
TITisresearch enahles us lo analyze from a geographic point ofview is territorial space ofLima Callao.noting urban set tins littlefuncttonal and devoid ofphvsical security in the road. It idcntifles urban transpon routes hightv vulnerable to a variety ofdangers, especiallv pollution.findtng urban arcas with l1igllpopulation densitv ami high concentration o/ vehicular also appreciate the environment, a largedeficit ofgreen areas.loss ofagriculrural laud ami/he impact(da dilapidated transportation system. JI is therefore important to consider the legal aspect 0// the issue ofurban transportoservicefor passengers and willfunher flotesduplication offunctions of the Public Institutions, which is inadequate to reality, thisprevents the management ofpublic transpon. which broadcast rulesand regulationswithout coordina/ion 01' technical consultations between the competen;authorities.